Novel axial oxygenator with bevelled shape of priming volume - Goubergrits Leonid; Franke Benedikt (Current Directions in Biomedical Engineering)
Oxygenators are a lifesaving technology used for blood oxygenation and decarboxylation in case of acute respiratory failure, chronic lung disease, and during open-heart surgery. Devices typically consist of a bundle of thousands of fibre membranes in a housing, with gas flowing inside the fibres and blood flowing in the opposite direction outside the fibres. Both ends of the fibre-membranes are fixed with an adhesive to separate gas and blood. The shape of the volume through which the blood flows is determined by the housing of the oxygenator and the internal end surfaces of the fixed ends of the fibre-membrane bundle. The traditional potting process results in a volume shape that is associated with stagnation zones, which are known to promote thrombus formation. In this study, an adapted potting process is proposed which results in a blood compartment with bevelled end faces of the glued bundle parts. Using a numerical study, we have demonstrated that the novel oxygenator design results in optimized flow conditions.